Iodine seed- versus wire-guided localization in breast-conserving surgery for non-palpable ductal carcinoma in situ. Issue 13 (22nd October 2015) - Luiten, J D; Beek, M A; Voogd, A C; Gobardhan, P D; Luiten, E J T
Abstract: Background: Breast-conserving surgery for isolated non-palpable ductal carcinoma in situ (DCIS) is associated with high rates of incomplete surgical resection in comparison with unifocal invasive breast cancer. Therefore, accurate preoperative localization of the lesion is very important to facilitate adequate resection. Wire-guided localization (WGL) remains the standard for localization of DCIS. Recently, iodine-125 seed-guided localization (I-125 GL) was introduced as an alternative localization technique. The aim of this study was to compare the efficacy of these localization techniques in the resection of DCIS by breast-conserving surgery. Methods: Between March 2006 and June 2013, 169 patients with non-palpable DCIS were treated with breast-conserving surgery. Only patients with pure DCIS on both preoperative core biopsy and definitive pathology were included. Results: WGL was performed in 78 patients and I-125 GL in 91 patients. The groups did not differ with respect to age, size of DCIS or type of imaging used. Patients in the I-125 GL group had a significantly lower risk of extensively involved resection margins than those in the WGL group (4 versus 13 per cent respectively; P = 0·048). Conclusion: In patients treated with breast-conserving surgery for non-palpable DCIS, localization with iodine-125 seeds is superior to the WGL technique in reducing the risk of extensively involved resection margins. Abstract : Seeds are superior